Perjalanan RUU KUHP Sebagai Hukum Baru yang Selaras Dengan Konstitusi dan HAM - Winarno; Agastya, Yoga; Prihantoro, Eko (Faculty of Law, Universitas Airlangga, 2024)
AbstractThis study examines the journey of Indonesian Criminal Law and the government's efforts to improve the law in Indonesia and focuses on the journey of the new law (RUU KUHP). Indonesia is a legal state consisting of 1,340 ethnic groups which have different customs, norms, and customary laws. Indonesia was colonized by the Dutch for 350 years and the legacy of Dutch law is still attached to the Indonesian state, namely the Criminal Code (book of criminal law). The Criminal Code that is applied in Indonesia also comes from continental law known as wetboek van strafrecht and applies as positive law in Indonesia to this day. The renewal of the Criminal Code aims to realize national criminal law based on Pancasila and the 1945 Constitution which is intended to replace the Criminal Code inherited from the Dutch Colonial State which is no longer in accordance with the times.Keywords: RUUKUHP; renewal; Constitution; Criminal. AbstrakKajian ini mengkaji perjalanan Hukum Pidana Indonesia dan upaya pemerintah untuk memperbaiki hukum di Indonesia dan menitikberatkan pada perjalanan hukum baru (RUU KUHP). Indonesia adalah negara hukum yang terdiri dari 1.340 suku bangsa yang memiliki adat istiadat, norma, dan hukum adat yang berbeda-beda. Indonesia dijajah Belanda selama 350 tahun dan warisan hukum Belanda masih melekat pada negara Indonesia yaitu KUHP (kitab hukum pidana). KUHP yang berlaku di Indonesia juga berasal dari hukum kontinental yang dikenal dengan wetboek van strafrecht dan berlaku sebagai hukum positif di Indonesia hingga saat ini. Pembaharuan KUHP bertujuan mewujudkan hukum pidana nasional berdasarkan Pancasila dan UUD 1945 yang dimaksudkan untuk menggantikan KUHP warisan Negara Kolonial Belanda yang sudah tidak sesuai lagi dengan perkembangan zaman.Kata Kunci: RUUKUHP; Pembaharuan; Konstitusi; Pidana.